A P.S. on B.S.: Some Remarks on Humbug and Bullshit. (7th January 2013) - Wreen, Michael
Abstract While lies have attracted philosophical attention since antiquity, phenomena in the near area have generated considerably less interest. Lately, however, Max Black and Harry Frankfurt have visited a close relative: humbug or bullshit, as it's either more politely or more rudely called. In this article their views on humbug and bullshit are exposed, explained, critiqued, and, ultimately, rejected. An alternative view is then proposed and defended.